X‐ray observations of the merging cluster CIZA J2242.8+5301. Issue 4 (2nd May 2013) - Ogrean, G.; Brüggen, M.; Simionescu, A.; Röttgering, H.; van Weeren, R.J.; Croston, J.H.; Hoeft, M.; Schartel, Norbert
Abstract Multiwavelength studies of radio relics at merger shocks set powerful constraints on the relics origin and formation mech‐anism. However, for X‐ray observations, a main difficulty is represented by the low X‐ray surface brightness far out in the cluster outskirts, where relics are typically found. Here, we present XMM‐Newton results from a 130‐ks observation of CIZA J2242.8+5301, a cluster at z = 0.19 that hosts a double radio relic. We focus on the well‐defined northern relic. There is a difference of ∼55% between the temperature we measure behind the relic, and the temperature measured with Suzaku. We analyse the reasons for this large discrepancy, and discuss the possibility of reliably measuring the temperature beyond the northern relic. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)